Morphological re-examination and taxonomy of the genus Macropodus (Perciformes, Osphronemidae) - Winstanley, Tom; Clements, Kendall D. (Zootaxa, 2008)
The taxonomy of the paradisefishes of the genus Macropodus (F. Osphronemidae) has been confused due to inadequate sampling and the limitations of morphometrics and meristics in distinguishing species. The validity of the five currently described species, including two species described in 2002, was investigated using morphological characters. These characters included 25 morphometric measurements, otolith morphology, colouration, and counts of scales, vertebrae and spines in unpaired fins. Samples were collected from the described distributions of M. spechti Schreitmüller, 1936 and M. erythropterus Freyhof & Herder, 2002 in central Vietnam, and of M. hongkongensis Freyhof & Herder, 2002 in Hong Kong. Populations of M. hongkongensis were newly recorded in eastern Guangdong and Fujian Provinces, P.R. China. M. opercularis (Linnaeus, 1758) was also collected close to these locations and in the major intervening drainages. Macropodus ocellatus Cantor, 1842 was collected from Chongqing Municipality, China, and samples augmented by some museum specimens. The latter species could be distinguished from other species of the genus by both meristic and morphometric characters. The species M. spechti, M. erythropterus, M. hongkongensis and M. opercularis could not be reliably distinguished from each other by meristic and morphometric characters. Otolith morphology did not distinguish any species. Colouration discriminated all species except M. spechti / M. erythropterus. As a result, M. erythropterus Freyhof & Herder, 2002 was undiagnosable on the basis of morphology. The presence of M. hongkongensis in eastern Guangdong and Fujian Provinces, in addition to Hong Kong, indicates that distribution of this recently-described species clearly requires further investigation in south-eastern China.